PENERAPAN AKAD MURABAHAH DENGAN TAMBAHAN DENDA PADA KELOMPOK UKM BINAAN DI BANK TABUNGAN PENSIUNAN NASIONAL (BTPN) SYARIAH SURABAYA DALAM TINJAUAN HUKUM ISLAM - Pedagogita Rakhmah (Maliyah : Jurnal Hukum Bisnis Islam, 2015)
Murabahah in BTPN Syariah there are two contract, which contract that goes first is an agreement mura>bah}ah where banks provide financing to customers in accordance with that contained in the contract, then after the agreed contract mura>bah}ah, and then proceed with the contract wakalah which the bank authorizes the customer to purchase the desired item according to the contract agreed upon contract. According to the status of Islamic law in practice is allowed. Since the application of fines is intended to foster a sense of responsibility and discipline for every customer financing.